Time based versus strain based myocardial performance indices in hypertrophic cardiomyopathy, the merging role of left atrial strain. (27th July 2018) - Kobayashi, Yukari; Moneghetti, Kegan J; Bouajila, Sara; Stolfo, Davide; Finocchiaro, Gherardo; Kuznetsova, Tatiana; Liang, David; Schnittger, Ingela; Ashley, Euan; Wheeler, Matthew; Haddad, Francois
Abstract: Aims: The myocardial performance index (MPI) is a time-based index of global myocardial performance. In this study, we sought to compare the prognostic value of the MPI with other strain and remodelling indices in hypertrophic cardiomyopathy (HCM). Methods and results: We enrolled 126 patients with HCM and 50 age- and sex-matched controls. Along with traditional echocardiographic assessment, MPI, left ventricular global longitudinal strain (LVGLS), E / e ′ ratio, and total left atrial (LA) global strain (LAS) were also measured. Time-based MPI was calculated from flow or tissue-based pulse wave Doppler (PWD and TDI) as the (isovolumic-relaxation and contraction time)/systolic-time. We used hierarchical clustering and network analysis to better visualize the relationship between parameters. The primary endpoint was the composite of all-cause death, heart transplantation, left ventricular assist device implantation, and clinical worsening. Left ventricular outflow tract (LVOT) obstruction was present in 56% of patients. Compared with controls, patients with HCM had worse LVGLS (−14.0 ± 3.4% vs. −19.6 ± 1.5%), higher E / e ′ (12.9 ± 7.2 vs. 6.1 ± 1.5), LA volume index (LAVI) (36.4 ± 13.8 ml/m 2 vs. 25.6 ± 6.7 ml/m 2 ), and MPI (0.55 ± 0.17 vs. 0.40 ± 0.11 for PWD and 0.59 ± 0.22 vs. 0.46 ± 0.09 for TDI) (all P < 0.001). During a median follow-up of 55 months, 47 endpoints occurred. PWD or TDI-based MPI was not associated with outcome, while LAVI, LAS, LVGLS, and E / e ′ were (all P < 0.01). On multivariable analysis, LVOT obstruction ( P < 0.001), LAS ( P < 0.001), and E / e ′ ( P = 0.02) were retained as independent associates. They were in different clusters suggesting complemental relationship between them. Conclusion: Time-based index is less predictive of outcome than strain or tissue Doppler indices. LAS may be a promising prognostic marker in HCM.